Perjalanan Seni dan Budaya: Jejak Karya-Karya Raden Saleh dalam Perspektif Historis - Yandi Syaputra Hasibuan (Medan Resource Center, 2023)
Raden Saleh, a prominent Indonesian artist, has regained attention in recent times with the release of the film